PENGUATAN STANDAR KOMPETENSI LULUSAN MEMBACA SASTRA MELALUI STRATEGI META-ANALISIS BAGI MAHASISWA JURUSAN BAHASA DAN SASTRA INDONESIA - U'um Qomariyah (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2022)
At first, students' low literary reading experience became a thought to find effective strategies so that students were interested in reading and got the concept of learning experience by thinking critically. To achieve this kind of condition, students' familiarity with literary works accompanied by an understanding of critical reviews is absolutely necessary. Meta-analysis provides a strategy that can be used by lecturers to strengthen the Literature Reading Competency Standards (SKL). This study aims to reveal the use of meta-analysis strategies in strengthening SKL Reading Literature for students majoring in Language. This research uses descriptive analysis method. The data collection stage was carried out through literature study (critical review), interviews, and observations. The results showed that there was a correlation that could be correlated between the achievement of SKL Reading Literature through meta-analysis strategies. Furthermore, the meta-analysis learning design in Literature Reading SKL Achievement is carried out in four stages, namely determining the literary period (problem formulation), determining and selecting literary reading results, reading literary works, and presenting the literary reading meta-analysis report